Contextual Effect of Community Health Center and Other Determinants of Midwife Performance in the Implementation in the Prevention Mother to Child Transmission Counselling and Testing: A Multilevel Model Evidence - Sringatin Sringatin; Uki Retno Budihastuti; Endang Sutisna Sulaeman (Journal of Health Policy and Management, 2020)
Background: High transmission of HIV from mother to child can contribute to an increase in the number of pandemic events. Transmission of HIV from mother to baby can be prevented by the PMTCT (Prevention of Mother to Child HIV Transmission) program. The purpose of this study is to analyze the implementation of PMTCT program policies by midwives.Subjects and Method: The design used in this study was observational analytic with cross sectional approach. The number of samples is 184 subjects. The sampling was done using total sampling. The independent variables included midwives' knowledge, midwife's age, job satisfaction, team performance, work environment, community support, training, and length of work. Meanwhile, the dependent variable is the implementation of PMTCT policies. Variable data collection was performed using a questionnaire and analyzed using multilevel analysis with Stata 13.Results: The implementation of PMTCT policies increased influenced by period of working ≥8 years (b= 0.50; 95% CI= 0.61 to 0.85; p= 0.004), training ≥2 times (b= 0.44; 95% CI= -0.13 to 0.76; p= 0.005), good midwife knowledge (b= 0.65; 95% CI= 0.36 to 0.93; p<0.001), midwife satisfaction is good (b= 0.05; 95% CI= -0.21 to 0.31; p= 0.694), and midwife performance is good (b= 0.59; 95% CI= 0.25 to 0.93; p= 0.001). The implementation of PMTCT policies decreased influenced by bad working environment (b= -0.09; 95% CI= -0.36 to 0.16; p= 0.451), age ≥35 years (b= -0.51; 95% CI= -0.80 to -0.24; p<0.001), and small community support (b= -0.06; 95% CI= -0.38 to 0.25; p= 0.692). Public health ceneters have weak contextual influence on the implementation of PMTCT program policies with ICC= 6.6%.Conclusion:The midwife's period of work, knowledge, training, midwife's performance, and midwife's satisfaction improve PMTCT implementation. Whereas midwives' age, work environment and community support reduce PMTCT implementationKeywords: HIV / AIDS, implementation of PMTCT, multiple linear regression analysis.Correspondence:Sringatin, Dolopo Regional Public Hospital, Madiun, East Java. Jl. Raya Dolopo no.117 Dolopo, Madiun 63174, East Java. Email: sringatine22@gmail.com. Mobile: 081231683090Journal of Health Policy and Management (2020), 5(1): 35-47https://doi.org/10.26911/thejhpm.2020.05.01.04